In the city, out of place: nuisance, pollution, and dwelling in Delhi, c.1850-2000 - Sharan, Awadhendra (Oxford University Press, 2014)
This book is a contemporary history of environmental issues in Delhi. It traces the journey from the engagement with sanitary matters in the nineteenth century to issues of air and water pollution, waste and toxicity in contemporary Delhi. Matters of environmental improvement, it suggests, are synchronous in Indian cities rather than being separated in time and space, making them distinct from cities of the global North.